2013
DOI: 10.1371/journal.pone.0078107
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Infections Mimic Cryptic Speciation in Two Parasitic Butterfly Species, Phengaris teleius and P. nausithous (Lepidoptera: Lycaenidae)

Abstract: Deep mitochondrial divergence within species may result from cryptic speciation, from phylogeographic isolation or from endosymbiotic bacteria like Wolbachia that manipulate host reproduction. Phengaris butterflies are social parasites that spend most of their life in close relationship with ants. Previously, cryptic speciation has been hypothesised for two Phengaris species based on divergent mtDNA sequences. Since Phengaris species are highly endangered, the existence of cryptic species would have drastic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 91 publications
(109 reference statements)
1
67
0
Order By: Relevance
“…Ritter et al (2013) tested the theory of cryptic speciation on a comprehensive sample across the Palaearctic ranges and revealed that deep mitochondrial divergence did not correspond with microsatellite data but was concordant with Wolbachia infection in both species. Haplotypes previously attributed to cryptic species were part of Wolbachia- nausithous.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ritter et al (2013) tested the theory of cryptic speciation on a comprehensive sample across the Palaearctic ranges and revealed that deep mitochondrial divergence did not correspond with microsatellite data but was concordant with Wolbachia infection in both species. Haplotypes previously attributed to cryptic species were part of Wolbachia- nausithous.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial haplotype network which included also the sequences of Ritter et al (2013) (Fig. 1b).…”
Section: Wolbachia Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, several authors have pointed out that the phylogenetic studies, or species identification based on mtDNA alone, can be misleading as trees inferred from single markers sometimes display relationships that reflect the evolutionary history of individual genes rather than the species being studied (Ballard & Whitlock, 2004;Bensch et al, 2006). Moreover, mitochondrial introgression (Zakharov et al, 2009) and Wolbachia infection (Ritter et al, 2013) also can lead to erroneous phylogenetic reconstructions and species misidentification. Despite these limitations, level of genetic distances can provide indirect evidence for conspecifity/non-conspecifity of species being studied.…”
Section: Methodsmentioning
confidence: 99%